RNase H sequence preferences influence antisense oligonucleotide efficiency - Kiełpiński, Łukasz J. (Nucleic Acids Res, 2017)
RNase H cleaves RNA in RNA–DNA duplexes. It is present in all domains of life as well as in multiple viruses and is essential for mammalian development and for human immunodeficiency virus replication. Here, we developed a sequencing-based method to measure the cleavage of thousands of different RNA–DNA duplexes and thereby comprehensively characterized the sequence preferences of HIV-1, human and Escherichia coli RNase H enzymes. We find that the catalytic domains of E. coli and human RNase H have nearly identical sequence preferences, which correlate with the efficiency of RNase H-recruiting antisense oligonucleotides. The sequences preferred by HIV-1 RNase H are distributed in the HIV genome in a way suggesting selection for efficient RNA cleavage during replication. Our findings can be used to improve the design of RNase H-recruiting antisense oligonucleotides and show that sequence preferences of HIV-1 RNase H may have shaped evolution of the viral genome and contributed to the use of tRNA-Lys3 as primer during viral replication.